2017
DOI: 10.1002/jhet.2937
|View full text |Cite
|
Sign up to set email alerts
|

Ring Transformation of a 2(3H)‐furanone Derivative into Oxazinone and Pyrimidinone Heterocycles

Abstract: The conversion of the 2(3H)‐furanone into the oxazinone and pyrimidinone derivatives is studied. A 2‐(furan‐2‐ylmethylene)‐4‐oxo‐4‐phenylbutanoyl azide 3 was synthesized to carry out these conversions through its thermolysis in dry benzene and/or base‐catalyzed decomposition of this azide in the presence of different amines. The structures of all compounds were demonstrated from their spectral data and elemental analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 24 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…1 H NMR (d, ppm): 7.95-7.41 (m, 8H, Ar-H), 4.90 (s, 2H, CH 2 ), 4.15 (q, 2H, CH 3 CH 2 , J = 6.5 Hz), 1.21 (t, 3H, CH 2 CH 3 , J = 6.5 Hz). EIMS, m/z, (%): 345.41 (M + , 37), 272.30 (M + − COOC 2 H 5 , 49), 186.42 (26), 135.03 (23), 110.21 (30) N 0 -Dodecanoylthiophene-2-carbohydrazide (7). 44 A solution of thiophene-2-carbohydrazide 1 (1 mmol) and dodecanoyl chloride (1.1 mmol) in pyridine (5 mL) was heated in a water bath at ∼90 °C for 6 h. The reaction mixture was cooled to room temperature and then poured onto ice/HCl while stirring.…”
Section: Generalmentioning
confidence: 99%
See 1 more Smart Citation
“…1 H NMR (d, ppm): 7.95-7.41 (m, 8H, Ar-H), 4.90 (s, 2H, CH 2 ), 4.15 (q, 2H, CH 3 CH 2 , J = 6.5 Hz), 1.21 (t, 3H, CH 2 CH 3 , J = 6.5 Hz). EIMS, m/z, (%): 345.41 (M + , 37), 272.30 (M + − COOC 2 H 5 , 49), 186.42 (26), 135.03 (23), 110.21 (30) N 0 -Dodecanoylthiophene-2-carbohydrazide (7). 44 A solution of thiophene-2-carbohydrazide 1 (1 mmol) and dodecanoyl chloride (1.1 mmol) in pyridine (5 mL) was heated in a water bath at ∼90 °C for 6 h. The reaction mixture was cooled to room temperature and then poured onto ice/HCl while stirring.…”
Section: Generalmentioning
confidence: 99%
“…On the other hand, the acid hydrazides have been easily converted into hydrazones, oxadiazoles, triazoles, and various heterocycles. [7][8][9][10] Among the hydrazides, 2-thienohydrazides have received extensive attention due to the biological effects of thiophene moiety which were recognized and practically applied in herbicides, 11 fungicides, 12 and several agents. 13 Otherwise, it was shown that thiosemicarbazide derivatives provide various functionality through nucleophilic and electrophilic centers.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] Accordingly, furanones are found to be easily converted to a variety of heterocyclic skeletons of biological importance. [14][15][16][17][18][19][20] A broad range of pharmacological activities including insecticidal, antiviral, anticancer, antimicrobial, antimalarial, anti-inammatory, and analgesic properties have been documented in quinoline (benzo[b]pyridine) derivatives (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…These products have low toxicity in their application [7]. In turn, furan‐2(3 H )‐ones are of considerable interest as they are versatile key materials for synthesis of a variety of heterocycles having a diverse of pharmacological applications [8–18]. Furthermore, quinolin‐2(1 H )‐ones are of fascinating interest according to their role in natural products and their pharmacological effects [19–27].…”
Section: Introductionmentioning
confidence: 99%